Rogue One e Aquarius: o profissional arquivista sob o olhar do cinema - VILELA, José Augusto da Silva (2018)
This theoretical documentary work aims to make an approach to the representativeness of the archive environment and the archivist in the cinematographic world, using as study objects the films: Rogue One and Aquarius. To do this, we performed a film analysis of the two works and added the impressions with the area of archivology and professional performance in Brazil, by identifying if the archive elements and the professional archivist are presented in a satisfactory way to bring positive visibility to the area. A study was carried out on the emergence of archival discipline and its main foundations, as well as on the reality of the professional in Brazil, legislation covering the area and finally, a historical summary about cinema, its technologies and its main challenges in the century XXI. Then, after the analysis of the productions, it was verified that both films presented in a faithful way the archiving environment, but, when approaching the professional reality, they showed several practices that do not fit the assignments of the archivist. Finally, it is shown that the area is still not well represented in works of fiction, contributing to the lack of information society has on the role of the professional, however, the film industry has new productions every year, and perhaps in the future, there may be changes on the representations of the Archivology in the media, enhancing future research.